2011
DOI: 10.1016/j.ijimpeng.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Hard projectile penetration and trajectory stability

Abstract: Abstract:We present a general framework to describe the dynamics of a hard projectile penetrating into a solid target. Rigid-body dynamics, differential area force law and semi-empirical resistance function are used to formulate the motion of the hard projectile. The proposed model is capable of predicting the projectile trajectory under various oblique and yaw angles. Critical conditions for the occurrences of the instability and the reverse of the projectile trajectory are discussed. It was found that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Experimental results in [20] indicated the trajectory convergence, i.e. the projectile trajectory gradually becomes straight after a curvilinear motion in target medium, which has also been observed in [17]. However, this phenomenon was neglected in further studies.…”
Section: Waterways Experiments Station (Wes) To Develop 2-d (Penco2d) mentioning
confidence: 55%
See 4 more Smart Citations
“…Experimental results in [20] indicated the trajectory convergence, i.e. the projectile trajectory gradually becomes straight after a curvilinear motion in target medium, which has also been observed in [17]. However, this phenomenon was neglected in further studies.…”
Section: Waterways Experiments Station (Wes) To Develop 2-d (Penco2d) mentioning
confidence: 55%
“…[17][18][19][20][21]) based on DAFL approach and semi-empirical resistance function. It has been found that the projectile trajectory may change abruptly around a critical impact velocity, which was considered as a trajectory instability problem [17]. Experimental results in [20] indicated the trajectory convergence, i.e.…”
Section: Waterways Experiments Station (Wes) To Develop 2-d (Penco2d) mentioning
confidence: 99%
See 3 more Smart Citations